COMPLEX SIMPLICITY OF THE ART WORK BY LJUBINKA JOVANOVIĆ MIHAILOVIĆ (Heritage, 2023)
This paper analyzes the main features of Ljubinka Jovanović Mihailović's art work. The task was to point out the basic poetic properties of this painter's art work, but also its relative neglect. Analytical-synthetic method was used in this paper. The complex simplicity of her paintings was presented, the nature of her art objects was discussed and it was said that her art work in its cardinal flow belongs to abstract geometricism. Apostrophized, accordingly, have been also geometric sections, wide colored surfaces - often in color contrast between dark, ultramarine, purple, gold, silver colors, which makes a unique mix of picturesque chromatic changes in the painting of Ljubinka Jovanović Mihailović. The object reductionism of her paintings has been highlighted, as well as the coloristic symbiosis with Serbian-Byzantine frescoes and icons.
Keywords: art objects, lyrical abstraction, abstract geometricism, Byzantine iconography, Serbian-Byzantine fine art